UJI VALIDITAS KONSTRAK TES MINAT INDONESIA MELALUI KOMPONEN MINAT KESEHATAN - Jelpa Periantalo (Psycho Idea, 2018)
Indonesia Interest Test was a psychological test based on Indonesian’s culture, had an intellectual copyright from The Departement of Law, Republic of Indonesia in 2015. Test result could be used for high school majoring, university majoring, self development, employee selection and placement. The purpose of research was to examine construct validity from its component of health sciences interest.It was consisted of interest in medical, human anatomy, dentistry, nursing, pharmacy, nutrition, public health and microorganism. It used question with some answered and rating scale format with an orthogonal type of construct. The subjects of research consisted of junior high school, senior high school and university students. Convergent validity showed there was a positive correlation between healt interest with science and technology interest (rxy=0.665, p=0.000; p <0.01; N=388). Divergent validity showed there was a negative correlation between health interest and psychological interest (rxy=-0.370, p=0.000, p < 0.01;  N=390). Discrimiant validity showed there was no correlation between health interest and social humanity attitude scale (rxy=0.024, p=0.747; p < 0.05; N=177). Group validity showed there was a different of health interest between health science students and psychological science students  (t=11.824; p=0.000). Health science students had a higher interest in healt lebih tinggi (M=13.99; N=113) than psychological science students (M=2.63; N=76). The test had satisfied construct validity. The next researd was to examine with external criterion, such as: academic achievement, learning satisfaction and length of study Keywords:  Construct, Convergent, Discriminate, Divergent, Validity,Orthogonal